Agreement Between Invasive Wire-Based and Angiography-Based Vessel Fractional Flow Reserve Assessment on Intermediate Coronary Stenoses - Chang, Chun-Chin; Lee, Yin-Hao; Chuang, Ming-Ju; Hsueh, Chien-Hung; Lu, Ya-Wen; Tsai, Yi-Lin; Chou, Ruey-Hsing; Wu, Cheng-Hsueh; Lu, Tse-Min; Huang, Po-Hsun; Lin, Shing-Jong; van Geuns, Robert-Jan (Frontiers in Cardiovascular Medicine, 2021)
Background: Angiography-based functional assessment of coronary stenoses emerges as a novel approach to assess coronary physiology. We sought to investigate the agreement between invasive coronary wire-based fractional flow reserve (FFR), resting full-cycle ratio (RFR), and angiography-based vessel FFR (vFFR) for the functional assessment of coronary stenoses in patients with coronary artery disease. Materials and Methods: Between Jan 01, 2018, and Dec 31, 2020, 298 patients with 385 intermediate lesions received invasive coronary wire-based functional assessment (FFR, RFR or both) at a single tertiary medical center. Coronary lesions involving ostium or left main artery were excluded. vFFR analysis was performed retrospectively based on aortic root pressure and two angiographic projections. Results: In total, 236 patients with 291 lesions were eligible for vFFR analysis. FFR and RFR were performed in 258 and 162 lesions, respectively. The mean FFR, RFR and vFFR value were 0.84 ± 0.08, 0.90 ± 0.09, and 0.83 ± 0.10. vFFR was significantly correlated with FFR (r=0.708, P <0.001) and RFR (r=0.673, P<0.001). The diagnostic performance of vFFR versus FFR was accuracy 81.8%, sensitivity 77.4%, specificity 83.9%, positive predictive value 69.9%, and negative predictive value 88.5%. The discriminative power of vFFR for FFR ≤ 0.80 or RFR ≤ 0.89 was excellent. Area under the receiver operating characteristic curve (AUC) was 0.87 (95% CI:0.83-0.92) for FFR and 0.80 (95% CI:0.73-0.88) for RFR. Conclusion: Angiography-based vFFR has a substantial agreement with invasive wire-based FFR and RFR in patients with intermediate coronary stenoses. vFFR can be utilized to assess coronary physiology without a pressure wire in a post hoc manner.